Accelerating Drug Development Through Collaboration: The Hepatitis C Drug Development Advisory Group. Issue 2 (22nd May 2014) - Hutchison, C; Kwong, A; Ray, S; Struble, K; Swan, T; Miller, V
<x xml:space="preserve">Abstract</x> Over the past decade, landmark collaboration between regulatory agencies, pharmaceutical companies, academia, and patient community representatives has enabled the development and approval of new hepatitis C virus (HCV) treatment regimens with unprecedented speed. By providing a neutral platform for cross‐sector engagement, the Forum for Collaborative HIV Research's1 HCV Drug Development Advisory Group played a critical role in fostering this collaboration and expediting drug development. The applicability of this model to other therapeutic areas should be explored. Clinical Pharmacology & Therapeutics (2014); 96 2, 162–165. doi:10.1038/clpt.2014.113